PRO-REQ: a facilitator guide to implement CMMI-Dev requirements engineering and management areas - Diniz, Alfraino Souza; Sanches, Rosely; Braga, Rosana T. Vaccare (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2009: Anais do VIII Simpósio Brasileiro de Qualidade de Software, 2009)
Requirements engineering processes are among the major sources of problems found during software development. A way of reducing these problems is to introduce maturity models like CMMI, but they are more likely to define what has to be done, instead of how it should be done. This paper presents a guide whose goal is to facilitate the implementation of requirements engineering processes in organizations that cannot afford their expensive costs. The guide bases on CMMI practices, but also considers several other sources of good practices on requirements engineering and management. The results of applying it in a small Brazilian software development organization are also presented.